Highly Thermally Conductive and Flame-Retardant Waterborne Polyurethane Composites with 3D BNNS Bridging Structures via Magnetic Field Assistance - Hao Jiang; Yuhui Xie; Mukun He; Jindao Li; Feng Wu; Hua Guo; Yongqiang Guo; Delong Xie; Yi Mei; Junwei Gu (Nano-Micro Letters)
Highlights By simultaneously incorporating the magnetic filler-modified boron nitride nanosheets (M@BNNS) and the non-magnetic filler U-BNNS into the polymer matrix, a three-dimensional heat conduction pathway composites are obtained under a horizontal magnetic field. Owing to the microstructural design of the 3D-bridging architecture, with the addition of only 5 wt% U-BNNS, the λ ⊥ of composites achieved 2.88 W m−1 K−1, representing a remarkable increase of 194.2% compared to single-oriented composites. The 3D-bridging architecture composite also demonstrates excellent flame retardancy, attributed to the synergistic mechanisms of condensed and gas phases, effectively mitigating the risks of thermal runaway in electronic devices.